Aplikasi Hukum Coulomb dan Medan Listrik terhadap Kualitas Udara dalam Mobil Konvensional - Mohammad Elvanoky Fachrizky Galuh Saputra; Nurhidayatullah Nurhidayatullah; Rangga Arsyadani Wahyudi (Asosiasi Riset Ilmu Teknik Indonesia, 2024)
This article discusses the use of Coulomb's law and electric fields to improve air quality in conventional cars. This method utilizes electrostatic principles to attract and capture air pollutant particles. This research introduces the practical application of this concept by integrating electrostatic technology into car ventilation systems. Experimental results show significant improvements in the reduction of in-vehicle air pollutants, with the potential to improve the health and comfort of car users. With wider application, this technology can help reduce the negative impact of air pollution on the environment and human health.